PENGARUH HUBUNGAN KERJA SAMA DAN FASILITAS TERHADAP MINAT BERKUNJUNG DI GRAND KANAYA HOTEL MEDAN - Restinauli Natalia Panjaitan; Marupa Siregar (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
This research is motivated by a high growth rate of hotels which is not matched by an increase in the number of tourists. This of course will affect the number of visitors who visit the hotel. Hotel service providers must prepare the best strategy to attract visitors, because with the emergence of new hotels, visitors will have more choices. Hotel Grand Kanaya Medan is one of the hotels affected by this imbalance. The problems in this study are the objectives of this study are: (1) To determine the effect of cooperative relations on interest in visiting the Grand Kanaya Hotel Medan. (2) To determine the effect of facilities on interest in visiting the Grand Kanaya Hotel Medan. (3) To determine the effect of cooperation and facilities on interest in visiting the Grand Kanaya Hotel Medan.The results of this study indicate that: (1) There is an effect of cooperation on visiting interest with tcount> ttable = 4.355> 1.988 with a significant a (0.000 <0.05). (2) There is an effect of facilities on interest in visiting with the value of tcount> ttable = 5.598> 1.988 with a significant a (0.000 <0.05). (3) There is an effect of cooperation and facilities on visiting interest with the value fcount> ftabel = 40.886> 3.95 with a significant a (0.000 <0.05).